The Birth, Death, and Renaissance (?) of Dissection: A Critique of Anatomy Teaching With—or Without—the Human Body. (July 2020) - Marom, Assaf
Abstract : A riveting debate regarding the fate of dissection, the classical method of anatomy, is sweeping through medical academia, as imaging tools gain a greater foothold in anatomy teaching programs. This Perspective does not aim to grapple with the question of "how should anatomy be taught" but rather to explain why the transformation of anatomical education is taking place by situating these developments in the broader philosophical context of modern medicine, offered by Michel Foucault's The Birth of the Clinic: An Archaeology of Medical Perception . Emphasizing the body's crucial role in the epistemological change in medical practice in the early 19th century, Foucault coined the term "medical gaze" to denote the doctor's observation of the patient's body in search of signs of disease. Within this new systematic perception of disease, which brought about the anatomo-clinical method, the clinical gaze thus embraced the study of the body via dissection. The author contends that the introduction of medical imaging into the diagnostic process has resulted in a shift in the focus of the clinical gaze from the body to its medical image and that this process is mirrored in anatomy by its discarding of the cadaver. Given the fundamental differences between the phenomenology of the body and its medical image, the author suggests that when using medical images in medical schools and teaching hospitals, one teaches, at the very least, a new kind of anatomy. Foucault's analysis of the painting The Treachery of Images by Réne Magritte lends some support to the ideas presented here. Abstract : Supplemental Digital Content is available in the text.